Prefabrication and Prelamination Strategies for the Reconstruction of Complex Defects of Trachea and Larynx - Vranckx, J. J.; Den Hondt, M.; Delaere, P. (Journal of Reconstructive Microsurgery, 2014)
Complex tracheal and laryngeal defects can be reconstructed using prelamination and prefabrication techniques. Three clinical situations are described in detail in the article. In short segment restenosis defects within scarred surroundings, we restore the fibrocartilaginous defect with a radial forearm fascia flap prelaminated with buccal mucosa or cartilage. This provides a newly vascularized inner lining to the tracheal defect and restores the tubular convexity. For long segment defects we need a technique that can withstand respiratory forces. We use a heterotopic prefabrication strategy to vascularize a tracheal allograft wrapped in forearm fascia. Chimerism is created by replacing donor respiratory epithelium with buccal mucosa of the recipient. After orthotopic transfer, this chimerism allows immunosuppression to be tapered and stopped when bronchoscopy shows mucosal integrity of the new trachea, since the recipient epithelium replaces the allogeneic inner tracheal lining by means of a chronic rejection process. A distinct situation occurs after resection of a unilateral larynx tumor, which usually results in a total laryngectomy with loss of both vocal cords, since reconstruction of the hemilarynx is considered too complex. First, we prefabricate a nearby four-ring autologous tracheal segment using radial forearm fascia. In a second stage, this orthotopically vascularized trachea restores the laryngeal structure with the aim to conserve one vocal cord and thus speech. Orthotopic and heterotopic prelamination and prefabrication strategies offer efficient and reproducible solutions for the restoration of challenging short and long segment tracheal defects, as well as unilateral laryngeal defects. The series in this review article are based on previous studies and case reports. The level of evidence is III—“Study of nonconsecutive patients, without a universally applied gold standard: case-control study”.
Keywords: prefabrication; prelamination; trachea reconstruction; larynx reconstruction; trachea transplantation